AB0568 Can Speckle Tracking Echocardiography Dectect Left Subclinal Ventricular Dysfunction in Patients with Primary Sjogren Syndrome?. (9th June 2015) - Atzeni, F.; Galaverna, S.; Colombo, D.; Gianturco, L.; Boccassini, L.; Sarzi-Puttini, P.; Turiel, M.
Abstract : Background: We have previously shown that plasma asymmetric dimethylarginine (ADMA) levels and coronary flow reserve (CFR) are impaired in patients with pSS. Objectives: The aim of this study was to evaluate the left ventricular myocardial function using STE in patients with pSS and normal ejection fraction. Methods: The study involved 49 outpatients who fulfilled the American European Consensus criteria (AECG) criteria for pSS (14 males and 35 females; mean age 57±6.9 years), and 49 healthy controls matched in terms of age, gender and other anthropometric characteristics. Cardiovascular (CV) risk profiles were assessed by means of standard electrocardiography (ECG), conventional and stress trans-thoracic echocardography with the measurement of CFR, carotid ultrasonography and pulse wave velocity (PWV). Two-dimensional echocardiographic images were obtained using the apical 4-chamber view at a high frame rate of 70-80 frames/s, and three cardiac cycles were stored in cine-loop format for off-line analysis using commercially available QLAB 9 software (Philips Medical System, USA) in order to assess end-systolic LV longitudinal strain (ɛ). Results: All of the patients had pSS with extra-glandular systemic involvement: 30 were being treated with hydroxychloroquine (HCQ) 400 mg/day, 11 with azathioprine (AZA) at a mean dose of 150 mg/day (range 50-200 mg), and eight with methotrexate (MTX) at a mean dose of 7.5 mg/weekly. None of the patients showed any signs or symptoms of CV disease, pulmonary involvement, or any other complication. The patients' mean LVEF and E/A ratios were respectively 59.11±6.35% and 0.94±0.24, which were not significantly different from those of the controls (60.02±6.04% and 0.96±0.22); however, although within the normal range, their CFR was lower (median 2.70, IQR 2.40-2.90 vs 3.20, IQR 3.06-3.33; p <0.0001). The results of the speckle tracking analysis were significantly different between the two groups, with global longitudinal strain deformation in the apical 4-chamber view (Long. ɛ 4c) being significantly lower in the pSS patients (Long ɛ 4c %: median 15.28, IQR 12.33-16.21 vs 19.84, IQR 19.34-20.40; p <0.0001). Right and left pulse wave velocity (PWV) (PWV m/sec median 8.8, IQR 7.26-10.32 vs 6.86, IQR 6.66-7.10; p <0.0001) and right and left coronary intima media thickness (cIMT) (cIMT mm: median 0.6, IQR 0.51-0.72 vs 0.53, IQR 0.50-0.60; p =0.08) values were all higher in the pSS patients, but the differences of cIMT were not statistically significant Conclusions: LV myocardial longitudinal ɛ measured by means of speckle tracking echocardiography was impaired in pSS patients in the absence of any clinical evidence of CV disease and echocardiographic evaluations negative. This data suggests a myocardial alteration, but further studies involving a large number of patients are required to define more precise methods of assessing CV disease in population. Disclosure of Interest: None declared